Arabinosylation of recombinant human immunoglobulin-based protein therapeutics. Issue 4 (19th May 2017) - Hossler, Patrick; Chumsae, Christopher; Racicot, Christopher; Ouellette, David; Ibraghimov, Alexander; Serna, Daniel; Mora, Alessandro; McDermott, Sean; Labkovsky, Boris; Scesney, Susanne; Grinnell, Christine; Preston, Gregory; et al.
ABSTRACT: Protein glycosylation is arguably the paramount post-translational modification on recombinant glycoproteins, and highly cited in the literature for affecting the physiochemical properties and the efficacy of recombinant glycoprotein therapeutics. Glycosylation of human immunoglobulins follows a reasonably well-understood metabolic pathway, which gives rise to a diverse range of asparagine-linked (N-linked), or serine/threonine-linked (O-linked) glycans. In N-linked glycans, fucose levels have been shown to have an inverse relationship with the degree of antibody-dependent cell-mediated cytotoxicity, and high mannose levels have been implicated in potentially increasing immunogenicity and contributing to less favorable pharmacokinetic profiles. Here, we demonstrate a novel approach to potentially reduce the presence of high-mannose species in recombinant human immunoglobulin preparations, as well as facilitate an approximate 100% replacement of fucosylation with arabinosylation in Chinese hamster ovary cell culture through media supplementation with D-arabinose, an uncommonly used mammalian cell culture sugar substrate. The replacement of fucose with arabinose was very effective and practical to implement, since no cell line engineering or cellular adaptation strategies were required. Arabinosylated recombinant IgGs and the accompanying reduction in high mannose glycans, facilitated a reduction in dendritic cell uptake, increased FcγRIIIa signaling, and significantly increased the levels of ADCC. These aforementioned effects were without any adverse changes to various structural or functional attributes of multiple recombinant human antibodies and a bispecific DVD-Ig. Protein arabinosylation represents an expansion of the N-glycan code in mammalian expressed glycoproteins.